2014
DOI: 10.1007/s10616-014-9751-y
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic analysis and Dlk1-Dio3 locus epigenetic status of mouse embryonic stem cells during early passages

Abstract: Mouse embryonic stem (ES) cells are widely used in early development studies and for transgenic animal production; however, a stable karyotype is a prerequisite for their use. We derived 32 ES cell lines of outbred mice (129 9 BALB (1B), C57BL 9 1B, and DD 9 1B F1 hybrids). Pluripotency was assessed by utilizing stem-cell-marker gene expression, teratoma formation assays and the formation of chimeras. It was shown that only 21 of the 32 ES cell lines had a diploid modal number of chromosomes of 40. In these li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
(30 reference statements)
0
8
0
1
Order By: Relevance
“…Menzorov et al . found that mouse ESCs can contribute into teratoma and even in chimera although their Dlk1-Dio3 imprinting control region is hypomethylated [ 44 ]. This result is similar to our findings, which confirmed that poor methylation seems not to disturb ESCs pluripotency, but in our results, important paternally expressed genes in this imprinting region were up-regulated and positively related to ESCs differentiation ability, which indicated that methylation is not the only regulation mode for these genes in the Dlk1-Dio3 region.…”
Section: Discussionmentioning
confidence: 99%
“…Menzorov et al . found that mouse ESCs can contribute into teratoma and even in chimera although their Dlk1-Dio3 imprinting control region is hypomethylated [ 44 ]. This result is similar to our findings, which confirmed that poor methylation seems not to disturb ESCs pluripotency, but in our results, important paternally expressed genes in this imprinting region were up-regulated and positively related to ESCs differentiation ability, which indicated that methylation is not the only regulation mode for these genes in the Dlk1-Dio3 region.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were provided by the Center for Genetic Resources of Laboratory Animals (RFMEFI61914X0005, RFMEFI62114X0010) at ICG SB RAS. Cell culture was performed as described previously (Menzorov et al 2016…”
Section: Derivation and Characterization Of Mouse Es Cellsmentioning
confidence: 99%
“…Experiments were performed in the Center for Genetic Resources of Laboratory Animals (RFMEFI61914X0005, RFMEFI62114X0010) at ICG SB RAS. The protocol was described earlier (Menzorov, Pristyazhnyuk, Kizilova, Yunusova, Battulin, Zhelezova, Golubitsa and Serov, 2016).…”
Section: Generation and Analysis Of Teratomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Это делает необходимым постоянный мони-торинг кариотипа. Показано, например, что ЭСК мыши даже на ранних пассажах культивирования могут иметь нестабильный состав хромосом (Menzorov et al, 2016).…”
Section: характеристики депонируемых линий клетокunclassified